Guidelines for cellular and animal models of insulin resistance in type 2 diabetes. Issue 6 (10th November 2022) - Wen, Yuxi; Ouyang, Yuezhen; Liu, Yuanyuan; Zhong, Ruhui; Huang, Qihui; Zhao, Chao
Abstract: As a lifelong chronic metabolic disease, there is no effective method to completely eradicate diabetes. In the search for effective treatments, disease models are important as a means of revealing pathogenesis and screening for potentially useful drugs. Insulin resistance (IR) is closely linked to type 2 diabetes (T2D), and is not only the basis for the pathogenesis of T2D but also the main thread running through the disease. It is the key to preventing T2D for improving insulin sensitivity and improving IR. Therefore, the construction of IR models is an important technique in T2D research. Most studies have constructed models by actively manipulating cells or animals to simulate disease phenotypes that are similar to human pathogenesis. This guideline provides experimental details for the construction of IR cells and animal models, which is currently the most common, efficient, and stable models used in laboratories for most cells and animals. The guideline for constructing models can help reveal the pathogenesis of T2D and provide a basis for drug screening and development studies for IR‐related diseases.